Women's Rights In Afghanistan Under Taliban Rule 1996-2001 And 2021-2022: A Comparative Study (Journal of Namibian Studies : History Politics Culture, 2022)
The paper identifies issues of women's rights in Afghanistan. Before the Taliban female enjoy freedom and rights of equality but after the end of soviet rule emergence of the Taliban with the Islamic edicts women faced threats and hardships in every aspect of life. The main purpose of this paper is to find the women's rights-related issues that are faced in Afghanistan under the Taliban regime and the research question is a comparison of the earlier status to the current regime. In the qualitative research, secondary sources provide knowledge of the past rule of the Taliban left an evil impact not only on the Afghan community but also on the international community that’s why in the second ruling power system by using the primary source see Taliban under probe try to improve the condition of Women's rights but do not less the threats. Our main finding concise as possible to minor differences related to earlier regimes. Female can protest for rights with hope despite the fear of loss of life. The level of insecurity and inequality may be reduced with the help and favour of foreign countries.